PENDEKATAN INTEGRAL DALAM PSIKOTERAPI TRANSPERSONAL - Hendro Prabowo (Buletin Psikologi, 2008)
Consciousness has been a popular topic in transpersonal psychology although the reviews were more focused on level of consciousness and states of consciousness. Theories of consciousness level are heavily influenced by perenial phylosophy concerning universal elements of consciousness, that are body, mind, soul and spirit. Transpersonal psychology also integrates Western and Eastern approaches in explaining consciousness. Both traditions have a variety and richness of tehniques to reach the four level of body, mind, soul and spirit. Davis (2003) describes transpersonal psychology as psychology that fully integrates psychological concepts, theories, and methods with practices and subject matter of spiritual sciences. In other word, the integration involves both theoretical and practical domains. This paper describes transpersonal psychology’s efforts in integrating psychotherapy.